2018
DOI: 10.1016/j.joen.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Periodontal Disease Effect on Pulp Volume

Abstract: The findings of this study showed that periodontitis causes pulp volume to reduce by approximately 20%. The use of three-dimensional models provides better understanding of the dental anatomy before endodontic treatment and, consequently, improvement of treatment outcomes. Additional studies are needed to investigate the effect of periodontal disease on pulp volume and surface area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
(19 reference statements)
1
5
1
Order By: Relevance
“…Further studies could be conducted to determine the possible effects on age estimation in adolescent age. Other possible explanations of variable pulp volumes in middle age groups are periodontitis, estrogen receptors present in pulp thus enhancing dentine formation, tooth shape and size, gene expression in odontoblasts, hormonal homeostasis, and occlusal stress [23, 3537]. One of the most notable differences observed in pulp volumes occur in those over 55 years of age, who demonstrate a rapid reduction in pulp volume this study contrary to other studies [30, 31].…”
Section: Discussioncontrasting
confidence: 60%
“…Further studies could be conducted to determine the possible effects on age estimation in adolescent age. Other possible explanations of variable pulp volumes in middle age groups are periodontitis, estrogen receptors present in pulp thus enhancing dentine formation, tooth shape and size, gene expression in odontoblasts, hormonal homeostasis, and occlusal stress [23, 3537]. One of the most notable differences observed in pulp volumes occur in those over 55 years of age, who demonstrate a rapid reduction in pulp volume this study contrary to other studies [30, 31].…”
Section: Discussioncontrasting
confidence: 60%
“…Dentinal tubules, lateral/accessory canals, and apical foramen contribute to the invasion of infectious factors during the progress of chronic periodontitis. Pulp volume was also reported to be decreased by 20% . Thus, in this study, we confirmed the microstructural damage of cementum by SEM and detected increased levels of inflammatory factors IL‐1β and IL‐17 in the pulp of teeth with periodontitis.…”
Section: Discussionsupporting
confidence: 85%
“…Pulp volume was also reported to be decreased by 20%. 32 Thus, in this study, we F I G U R E 6 Change of autophagy in dental pulp. The LC3B and P62 levels were checked by IF; both markers were significantly increased in the pulp of teeth with periodontitis (A through D).…”
Section: Discussionmentioning
confidence: 96%
“…Healthy teeth that do not have a pathological history can be used for age estimation in forensic medicine. 1,2 Periapical radiographs are not suitable for evaluating the pretreatment pulp cavity or endodontic treatment effect on the pulp cavity because superimposing the shadows of the structures causes misinterpretation of the periapical radiograph. 3 Cone-beam computed tomography (CBCT), a three-dimensional (3D) radiographic technique, is the most suitable method for evaluating pulp volume.…”
Section: Introductionmentioning
confidence: 99%
“…In cases where the clinical presentation of pathological components, such as trauma and caries, affects the pulp, pulp volume is an important indicator, especially for the treatment areas of dentistry. Healthy teeth that do not have a pathological history can be used for age estimation in forensic medicine 1,2 …”
Section: Introductionmentioning
confidence: 99%